A Review on the Magical Plant : Shatavari (Asparagus racemosus) - Maya Sharma; Ranu Sharma; P.K.Choudhury; Ankit Paliwal; Anukraman Singh; Dileep Kumar (Recent Trends in Cosmetics, 2025)
Shatavari (Asparagus racemosus) is a revered medicinal herb in Ayurveda, recognized for its diverse health benefits, particularly for women’s health. The chemical makeup, pharmacological characteristics, and therapeutic uses of shatavari are thoroughly examined in this review. Key active compounds include saponins, flavonoids, and phytoestrogens, which contribute to its adaptogenic, antioxidant, and hormone-regulating effects. These properties make Shatavari effective in addressing female reproductive issues, such as infertility, irregular menstrual cycles, and hormonal imbalances, by enhancing ovulation, uterine health, and cervical mucus production. Its adaptogenic properties also lessen reproductive issues brought on by stress. For skin renewal, shatavari has great promise beyond reproductive health. By encouraging the formation of collagen and supporting hydration, hormonal balance, detoxification, and scar healing, it improves skin texture and lessens the appearance of aging. Its ability to reduce inflammation and preserve the health of the skin is further supported by its anti-inflammatory and antioxidant qualities. Its safety and effectiveness have been shown by previous research, but more research is necessary to define standardized dosages and completely comprehend its mechanisms of action. This review underscores Shatavari's potential as a natural, multifaceted remedy for enhancing women's health and overall well-being, advocating for its integration into traditional and alternative medicinal practices under professional guidance.
Keywords: Herbal Cosmetics; Hormonal balance and skin health; Shatavari; Women’s health and skin wellness; reproductive health; skin rejuvenation; traditional medicine